Wear comfort properties of ZrC/Al2O3/graphite-embedded, heat-storage woven fabrics for garments. Issue 8 (April 2019) - Kim, Hyun Ah; Kim, Seung Jin
This study examined the different wear comfort properties of ZrC/graphite and Al2 O3 /graphite-embedded, heat-storage woven fabrics. ZrC/graphite and Al2 O3 /graphite-embedded, heat-storage polyethylene terephthalate (PET) filaments were spun on the pilot spinning equipment. The various wear comfort properties of the ceramic-embedded fabrics made from ZrC/graphite and Al2 O3 /graphite-embedded filaments were measured and compared with those of the regular PET/polyamide (PA) woven fabric. Surface temperatures of the ZrC/graphite and Al2 O3 /graphite-embedded fabrics, when irradiated by the light of a heat-emission bulb, were 5.1℃ and 8.4℃ higher than that of the regular PET/PA fabric, respectively. The water-absorption rate of the ceramic-embedded fabrics was 5 and 14 times higher than that of the regular PET/PA fabric, respectively. The breathability by the water vapor resistance ( R ef ) of the ZrC/graphite-embedded fabric was superior to that of the regular PET/PA fabric. The heat-retention rates of the ceramic-embedded fabrics were more than two times higher than that of regular PET/PA fabrics. Furthermore, the Clo value of the ZrC/graphite-embedded fabric by the thermal manikin experiment was more than 10% higher than that of the Al2 O3 /graphite and regular PET/PA fabrics. The skin and microclimate temperatures of the ZrC/graphite-embedded fabrics during the wearer trial were higher than those of the Al2 O3 /graphite and regular PET/PA fabrics, which revealed the good heat-storage and -release properties of the ZrC/graphite-embedded fabric. However, the Al2 O3 particles embedded in the yarns were assumed to give a unpleasant tactile effects.